Clinical Presentation of Ovarian Tumour - Nawrozy, MS; Sultana, F; Kamal, AHM; Begum, A; Tasmin, SF; Nahaer, MK (TAJ: Journal of Teachers Association, 2018)
Background: Clinical course of ovarian tumours are amazingly quite and the malignant ones are often inoperable by the time they are diagnosed. Aim of this study was to look into any probable way of early diagnosis of ovarian tumour. Methods: This study was carried out at the Department of Obstetrics & Gynaecology of Rangpur Medical College Hospital, Rangpur from July 2012 to June 2014. In this study, total 31 cases were included. The findings were described as percentage of total. In addition, χ2 test & Pearson’s correlation coefficient ‘r’ test were also used. Results: Age range of all the cases was between 16 and 65 years. Among the 31 cases, benign cases were 77.41% and malignant were 22.59%. The highest incidence of benign case was observed around 35 years of age and for the malignant cases was above 60 years. Patients commonly presented with abdominal lump (83.87%), abdominal pain (83.87%) and dyspepsia (74.19%). Other presentations were weight loss (22.58%), rapid enlargement of growth (16.13%), sense of heaviness of abdomen (9.67%) and abdominal enlargement (3.23%). Histologically serous cystadenoma was 38.71%, dermoid cyst 22.58%, mucinous cystadenoma 16.13%, poorly differentiated adenocarcinoma 12.90%, serous cyst adenocarcinoma 6.45% and immature teratoma was 3.23%. Conclusion: This sample is too small to draw any conclusion. Yet, as it was found, the incidence of benign tumours rises with increasing age up to 40 years and thereafter it declines. Whereas, the incidence of malignant tumours are very low before 40 years and thereafter it increases gradually. Also, public awareness may be developed regarding a female, specifically above 40 years of age, if complaints of abdominal lump, abdominal pain or dyspepsia should be evaluated properly; this may help in early diagnosis of many malignant ovarian tumours. TAJ 2015; 28(1): 21-25